Axioms of real numbers, and the beginning teaching of the analysis - Puriuškis, Gintaras (Lietuvos matematikos rinkinys, 2014)
This paper provides an overview of the definitions of real numbers. We pose the axiomatic definition of correctness question. Provided examples of sets that are consistent with some definitions of real numbers, but not in with us usual set of real numbers. Attention is drawn to the mathematical analysis of teaching beginning and claims proof of clearance.